2019
DOI: 10.1039/c9ob00162j
|View full text |Cite
|
Sign up to set email alerts
|

Conformational flexibility influences structure–function relationships in nucleic acidN-methyl demethylases

Abstract: Distinct conformational effects influence structure-function correlations in AlkB and FTO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
(84 reference statements)
1
15
0
Order By: Relevance
“…Details of the mechanism leading to the ferryl intermediate and studies on model systems have been reported [15– 26a] . Following substrate binding, the consensus 2OG oxygenase mechanism [7,12– 26a–c] involves initial generation of a Fe(III)‐superoxo complex; oxidative decarboxylation of 2OG generates a Fe(II)‐peroxysuccinate intermediate which reacts to give a high‐spin (S=2) state ferryl intermediate, which abstracts a hydrogen atom from the substrate. Hydrogen atom transfer (HAT) through a high spin surface is favored by spin exchange enhanced reactivity at the transition state, [27,28a] generating an Fe(III)‐hydroxyl intermediate that undergoes a low barrier hydroxyl rebound reaction with the substrate radical carbon to complete hydroxylation [Scheme 1].…”
Section: Introductionmentioning
confidence: 99%
“…Details of the mechanism leading to the ferryl intermediate and studies on model systems have been reported [15– 26a] . Following substrate binding, the consensus 2OG oxygenase mechanism [7,12– 26a–c] involves initial generation of a Fe(III)‐superoxo complex; oxidative decarboxylation of 2OG generates a Fe(II)‐peroxysuccinate intermediate which reacts to give a high‐spin (S=2) state ferryl intermediate, which abstracts a hydrogen atom from the substrate. Hydrogen atom transfer (HAT) through a high spin surface is favored by spin exchange enhanced reactivity at the transition state, [27,28a] generating an Fe(III)‐hydroxyl intermediate that undergoes a low barrier hydroxyl rebound reaction with the substrate radical carbon to complete hydroxylation [Scheme 1].…”
Section: Introductionmentioning
confidence: 99%
“…Because the conformational dynamics play an important role in the catalysis by the AlkB dioxygenase [15][16][17][18], it would be interesting to correlate specific conformational transitions of the enzyme-substrate complex with the individual steps of the process. Earlier, we applied the stopped-flow (SF) kinetic analysis of conformational dynamics to several repair DNA glycosylases and apurinic/apyrimidinic endonucleases as well as their DNA substrates to demonstrate how conformational rearrangements induce and follow the recognition, binding, and chemical events [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…When co-expressed as separate polypeptides in E. coli , these domains formed a stable complex [ 18 ]. Additionally, computational studies of Waheed and coworkers have revealed that the N- and C-terminal domains move with respect to one another in a manner likely important for substrate binding [ 44 ]. Therefore, testing the influence of the dimerization on activity by mutating amino acids in the C-terminal domain would be questionable.…”
Section: Discussionmentioning
confidence: 99%